Penyembunyian Pesan Rahasia Pada Citra Digital dengan Teknik Steganografi Menggunakan Metode Least Significant Bit (LSB ) - Lasarus Pelipus Malese (Peneliti.net, 2021)
The rapid development of digital media and its use in various fields raises greater demands to create an information delivery system that is guaranteed to be secure. One of them is with steganography. Steganography is a method for inserting pieces of confidential information in an object or other media. With steganography, information is hidden in such a way that its whereabouts are unknown, which is known as information hiding. This method is different from the cryptographic method, which encodes existing information so that it cannot be read without knowing the key or password used, but its existence is still known and not hidden. This final project was developed using Microsoft Visual Basic 6.0 implementing the Simple Least Significant Bit Substitution (